Stable Mo/HZSM-5 methane dehydroaromatization catalysts optimized for high-temperature calcination-regeneration - Kosinov, Nikolay; Coumans, Ferdy J.A.G.; Li, Guanna; Uslamin, Evgeny; Mezari, Brahim; Wijpkema, Alexandra S.G.; Pidko, Evgeny A.; Hensen, Emiel J.M. (Journal of catalysis, 2017)
[Display omitted] •High-temperature stability of Mo/HZSM-5 composite studied.•Mo content is the key parameter.•Novel isothermal (700°C) reaction – air regeneration protocol developed.•Optimized catalyst retained more than 50% of activity after 1week of operation. Dehydroaromatization of methane is a promising reaction to directly convert methane into aromatics and hydrogen. The main drawback of this reaction is the rapid deactivation of the Mo/HZSM-5 catalyst due to coking. Regeneration at high reaction temperature by air calcination is not possible due to extensive dealumination of the zeolite. We investigated the structural and textural stability of HZSM-5 as a function of the Mo loading in air at high temperature (550–700°C) and demonstrated that lowering the Mo loading below 2wt% greatly improves the oxidative stability of Mo/HZSM-5. At low Mo loading (1–2wt% Mo), Mo is predominantly in the zeolite micropores as cationic mono- and dinuclear Mo-oxo complexes irrespective of the calcination temperature. At higher loading, most of the initially aggregated Mo-oxide at the external surface is dispersed into the micropores upon calcination above 550°C, resulting in reaction of mobile MoO3 species with framework Al, aluminum molybdate formation and irreversible damage to the zeolite framework. A DFT-based free energy analysis indicates that water formation from reaction of MoO3 with Brønsted acid sites and high concentration of Mo during MoO3 migration causes aluminum molybdate formation. The high oxidative stability of Mo/HZSM-5 with low Mo loading makes them suitable candidates for a novel isothermal (700°C) reaction – air regeneration protocol of methane dehydroaromatization. Whereas a 5wt% Mo/HZSM-5 rapidly lost its initial activity, an optimized 2wt% Mo/HZSM-5 catalyst retained more than 50% of its initial activity after 100 reaction-regeneration cycles (1week) with a substantially improved total aromatics yield.